Expectations and aspirations : a new framework for education in the Middle East and North Africa - El-Kogali, Safaa; Krafft, Caroline (World Bank e-Library., 2020)
Education, which has been at the heart of the Middle East and North Africa (MENA) region's history and civilizations for centuries, has a large untapped potential to contribute to human capital, well-being, and wealth. The region has invested heavily in education for decades, but it has not been able to reap the benefits of its investments. Despite a series of reforms, MENA has remained stuck in a low-learning, low-skills level. This publication identifies four key sets of tensions that are holding back education in the region: credentials and skills, discipline and inquiry, control and autonomy, and tradition and modernity. These tensions are shaped by society and are reflected in classrooms. If they are not addressed, MENA will continue to operate at a level below its potential. This report outlines a new framework with a three-pronged approach that can help address these tensions and unleash the potential of education in MENA: --A concerted push for learning that starts early for all children regardless of background, with qualified and motivated educators, and that leverages technology, uses modern approaches, and monitors learning outcomes --A stronger pull for skills by all stakeholders in the labor market and society that involves coordinated multisystem reforms within and beyond the education system --A new pact for education at the national level with a unified vision, shared responsibilities, and accountabilities. Education is not just the responsibility of the education system-it is everyone's business. The push, pull, and pact framework offers an opportunity for MENA to move forward to reclaim its heritage of a learned region and to meet the expectations and aspirations of its people. The current situation in MENA requires a renewed focus on education, not just as a national priority for economic growth and social development, but as a national emergency for stability, peace, and prosperity.